CYP2A6 Polymorphisms May Strengthen Individualized Treatment for Nicotine Dependence - Yawo Mawuli Akrodou (Scientifica)
Each CYP2A6 gene variant metabolizes nicotine differently depending on its enzymatic activities. The normal nicotine metabolizer CYP2A6*1A is associated with high scores of nicotine dependence (5–10) on the Fagerström Test for Nicotine Dependence (FTND) scale because it encodes for enzymes that catalyze nicotine 100%. Slow nicotine metabolizers (i.e., CYP2A6*1H, CYP2A6*4A, CYP2A6*9, and CYP2A6*12A) are associated with underrated nicotine metabolizing activity (50%–75%), linking them to low scores for nicotine dependence (0–4) on the FTND scale. In a clinical trial involving the use of bupropion, people who were carriers of slow nicotine metabolizers were found to have a tendency to maintain abstinence 1.7 times longer than people with normal nicotine metabolizers. An overview of CYP2A6 polymorphism enzymatic activities in nicotine dependence etiology and treatment revealed that slow nicotine metabolizers may strengthen the individualized treatment of nicotine dependence.